Multi‐speckle X‐ray photon correlation spectroscopy in the ultra‐small‐angle X‐ray scattering range. (15th June 2016) - Möller, Johannes; Chushkin, Yuriy; Prevost, Sylvain; Narayanan, Theyencheri
Abstract : The feasibility for multi‐speckle XPCS measurements in the ultra‐low‐angle range is demonstrated. The performance of the setup is illustrated by means of colloidal dynamics. Abstract : Multi‐speckle X‐ray photon correlation spectroscopy (XPCS) measurements in the ultra‐small‐angle range are performed using a long pinhole collimation instrument in combination with two‐dimensional photon‐counting and high‐sensitivity imaging detectors. The feasibility of the presented setup to measure dynamics on different time and length scales pertinent to colloidal systems is shown. This setup offers new research opportunities, such as for example in the investigation of non‐equilibrium dynamics in optically opaque, complex systems over length scales from tens of nanometres to several micrometres. In addition, due to the short duration of the X‐ray exposure involved in the ultra‐small‐angle range, possible radiation‐induced effects are alleviated. Furthermore, the performance of two different detectors, a photon‐counting Pilatus 300K and an integrating FReLoN CCD, are compared, and their applicability for accurate XPCS measurements is demonstrated.